Ferroelectricity in glycine: A mini-review - Zelenovskii, Pavel S.; Vasileva, Daria S.; Vasilev, Semen G.; Kopyl, Svitlana; Kholkin, Andrei (Frontiers in Materials, 2022)
Glycine is the simplest natural amino acid, a basic building block for various biomaterials. Supramolecular packing of glycine molecules into three main crystalline polymorphs allows controlling their functional properties, such as piezoelectricity and ferroelectricity. Though piezoelectricity in glycine is well studied and reviewed, its ferroelectric properties were not summarized and analyzed until now. In this mini-review, we briefly discuss glycine polymorphs, their functional properties, and phase transitions, review recent findings on domain structure and polarization switching in β- and γ-glycine, and consider their possible applications in biocompatible photonic and piezoelectric devices.